Approaching the Intrinsic Threshold Breakdown Voltage and Ultrahigh Gain in a Graphite/InSe Schottky Photodetector. Issue 47 (17th October 2022) - Zhang, Zhiyi; Cheng, Bin; Lim, Jeremy; Gao, Anyuan; Lyu, Lingyuan; Cao, Tianjun; Wang, Shuang; Li, Zhu‐An; Wu, Qingyun; Ang, Lay Kee; Ang, Yee Sin; Liang, Shi‐Jun; et al.
Abstract: Realizing both ultralow breakdown voltage and ultrahigh gain is one of the major challenges in the development of high‐performance avalanche photodetector. Here, it is reported that an ultrahigh avalanche gain of 3 × 10 5 can be realized in the graphite/InSe Schottky photodetector at a breakdown voltage down to 5.5 V. Remarkably, the threshold breakdown voltage can be further reduced down to 1.8 V by raising the operating temperature, approaching the theoretical limit of 1.5 E g \[{{\cal E}_{\bf g}}\] / e, with E g ${{\cal E}_{\bf g}}$ the bandgap of semiconductor. A 2D impact ionization model is developed and it is uncovered that observation of high gain at low breakdown voltage arises from reduced dimensionality of electron–phonon scattering in the layered InSe flake. These findings open up a promising avenue for developing novel weak‐light detectors with low energy consumption and high sensitivity. Abstract : Intrinsic threshold breakdown voltage with an ultrahigh gain is observed in an avalanche photodetector (APD) based on a graphite/InSe Schottky junction, which is attributed to the high ionization rate due to the reduced dimensionality of electron–phonon scattering in layered InSe. This work opens up a new avenue for future APDs with both low energy consumption and high sensitivity.